1989
DOI: 10.1099/00222615-29-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Candida species and C. albicans biotypes in women attending clinics in genitourinary medicine

Abstract: Summary. Yeasts were isolated from two or more anatomical sites in 198 women attending genitourinary clinics on at least two occasions. The yeast biotypes isolated concurrently from the vagina and urethra were the same in 138 (99%) of 140 instances, and 94% of 124 concurrent genital and anal isolates were of matching types, whereas only 75% of concurrent genital and oral isolates were of the same type. Mixtures of Candida spp. or C. albicans biotypes were encountered only five times among 545 yeast-positive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…In the original application of this method to oral and vaginal isolates, 45 different types were identified (240), but the system had the potential for discriminating 512 types. The use of this biotyping strategy proved effective in a number of epidemiological studies (see, e.g., references 166,189,235,244,245,247,248,276,342, and 434), and if care was taken in standardizing methods, intralaboratory reproducibility could be achieved. Unfortunately, the Odds and Abbott biotyping system was found to have poor interlaboratory reproducibility among five laboratories (242).…”
Section: Biotyping Is Inadequate As a Dna Fingerprinting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original application of this method to oral and vaginal isolates, 45 different types were identified (240), but the system had the potential for discriminating 512 types. The use of this biotyping strategy proved effective in a number of epidemiological studies (see, e.g., references 166,189,235,244,245,247,248,276,342, and 434), and if care was taken in standardizing methods, intralaboratory reproducibility could be achieved. Unfortunately, the Odds and Abbott biotyping system was found to have poor interlaboratory reproducibility among five laboratories (242).…”
Section: Biotyping Is Inadequate As a Dna Fingerprinting Methodsmentioning
confidence: 99%
“…For instance, C. albicans strain WO-1 switches reversibly and spontaneously at frequencies of approximately 10 Ϫ3 between hemispheric white and flatter grey (opaque) colony phenotypes (345). The white-opaque transition results in dramatic changes in a variety of cellular traits (4,351,356) and the activation-deactivation of several white and opaque phase-specific genes (143,232,233,248,353,354,367,418). White-phase cells will assimilate ribitol, xylitol, methyl-D-glucoside, and trehalose, but opaque-phase cells will not (350), and this pattern changes in a perfectly reversible fashion with each spontaneous switch.…”
Section: Biotyping Is Inadequate As a Dna Fingerprinting Methodsmentioning
confidence: 99%
“…16 According to the authors, the evidence does not support strain tropism-a selection for "vaginotropic" vs. "vaginopathic" strains-since strains isolated during infection are statistically identical to those collected in asymptomatic colonization. 16,17 Using these same biotyping methods Odds et al 17,18 reported consistency in isolates from different sites (and tissue types) in the same patient and isolates collected months apart. Using different methods, a separate group also reported that no significant differences exist among Candida strains isolated from different body sites; but added that a single host can be colonized by multiple species, and even multiple genotypes of the same species.…”
Section: Mycology Of the Vaginamentioning
confidence: 99%
“…The protocol was modified by Childress et al (1989) to make it more amenable to general use. This biotyping strategy was effectively used in a number of epidemiological studies (Odds et al 1987, 1989b; Korting et al 1988; Poirier et al 1990; Xu & Samaranayake 1995; Lipperheide et al 1996). However, the system was found to have poor interlaboratory reproducibility (Odds et al 1989a); the use of the biotyping method in clinical research is therefore limited.…”
Section: Biotying Based On Phenotypic Charactersmentioning
confidence: 99%